La Gobernanza del agua y su calidad en tres acueductos de Villavicencio (Colombia) (2019)
Water governance proposes the taking of decisions that lead to the appropriation of a good service. The aim is to analyse the aspects related to this issue in relation to the quality of the liquid and its impact on health in households in commune 8 of Villavicencio Colombia. DANE data, laboratory results carried out by the Secretary of Health of the Department of Meta and a survey applied to 600 people were analyzed. As a result, problems related to potability, care of aqueducts, water quality and scarce citizen participation are factors that propose a bad state of governance in this context. © 2019 Revista ESPACIOS.